EFFECT OF ORGANIZATIONAL COMMITMENT AND EMPLOYEE WORKLOAD ON TURNOVER INTENTION AT PT DHANAR MAS CONCERN - Lestari, Nababan, Maria Dinda; Hernandya, Vania Nayunda; Hamidah, Ghina Sabrina; Syukriati, Hijri; Fauziah, Ajeng Nurul; Oktafien, Shinta (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to specify : 1) The Effectt of Organizational Commitment and Employee Workload on Turnover Intention of Employees at PT Dhanar Mas Concern 2) The Effect Organizational Commitment on Turnover Intention at PT Dhanar Mas Concern 3) The Effect of Employee Workload on Turnover Intention at PT Dhanar Mas Concern. This research is a causal associative research using a quantitative approach. This research with 294 respondents is a study where the sample is taken using a cluster random sampling technique, where the researcher divides several population groups or is called a cluster. The group or cluster is divided based on the fields that exist in the company, such as: Personnel Staff or HRD, Finance Staff, Production Staff, and staff who work in the field of Spinning and Weaving. In this research, data was collected using questionnaries, observations, internships, and interviews with one of the employee at PT Dhanar Mas Concern, while analysis data was carried out using correlation analysis and multiple linear regression. In this research the results of the data are normally distributed, the data is valid and reliable. The results of the study with a level of 5% indicate that: 1) Organizational Commitment and Employee Workload have a positive and significant effect on Turnover Intention 2) Organizational Commitment has a positive and significant effect on Turnover Intention 3) Employee Workload has a positive effect on Turnover Intention.